Faris Michaele: Trajectory of a modern intellectual (Olhar de Professor, 2011)
This article aims to analyze Faris Antônio Salomão Michaele’s intellectual trajectory (1911-1977) and discuss his conception of education. Faris Michaele was born in a borough called Mococa which is located in the countryside of Sao Paulo. When he was a child, his family moved to Ponta Grossa where he began to study at Colégio São Luiz (primary school), continued at Colégio Regente Feijó (secondary school) and graduated at Faculdade de Direito do Paraná. Michaele is recognized for participating and directing the creation of many spaces dedicated to culture and education such as Centro Cultural Euclides da Cunha (1947) and Faculdade de Filosofia, Ciências e Letras de Ponta Grossa (1949). He is also known for working as a secondary school teacher and a professor in Higher Education. The analysis of this character is based on Bourdieu and on the correspondences exchanged by Centro Cultural Euclides da Cunha and Faris Michaele. It is also based on the titles that compose his private library as well as on the articles written by him and about him. In the light of Bourdieu’s concepts and on the corpus it is possible to assert that Faris Michaele together with a social class which held the cultural capital established a number of institutions with the purpose of agglutinating part of Campos Gerais intellectuality and disseminating a worldview systematized by philosophy, science, literature and educational doctrines that were associated to the anthropocentric tradition.
Keywords: Faris Michaele. Intellectual trajectory. Education. Modernity.